Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Chrysidoidea, Sclerogibbidae - Olmi, Massimo (Zootaxa, 2020)
An updated checklist of the Arabian species of Sclerogibbidae is provided here. The list includes nine identified valid species in three genera of Sclerogibbinae. Distributions, both on the Peninsula and extra-limital, are provided for each species, three being new country records; none is endemic to the Arabian Peninsula.